AKTIVITAS ANTIFUNGI TEMU PUTIH (Curcuma zedoaria) TERHADAP Trichophyton mentagrophytes - Nuryanti, Siska (Jurnal Ilmiah As-Syifaa, 2016)
Curcuma zedoaria has long been known to be used in treatment of dermatophytosis; a skin disease caused by dermatophytes fungi such as Trichophyton mentagrophytes.The fungi infects hairs, skins, and nails that contain keratin. The study was conducted in order to measure the effect of ethanol extract of curcuma zedoaria in inhibiting Trichophyton mentagrohytes colonies. Results showed that the curcuma zedoaria ekstract inhibited Trichophyton mentagrophytes. The research was continued by Minimum Inhibitory Concentration (MIC) test by liquid dilution method in Sabaroud Dekstrosa Broth. Ethanol extract curcuma zedoaria did not indicate the value of the MIC test  because due to the color and viscosity of samples which interfere with the observations. As for the positive control shows a clear color, that  indicating the presence of inhibitory Trichophyton mentagrophytes by ketokonazol. For the value of the Minimum Fungicidal Concentration (MFC) to Trichophyton mentagrophytes are present in a concentration of 50%.